PENGARUH PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN DAN KOMPETENSI TERHADAP KINERJA MANAJERIAL - Prisca Patricia Liem (Paulus Journal of Accounting (PJA), 2022)
The purpose of this study is to look at the effect of applyingaccountability accounting and competence to the managerial performance ofPT. Pegadaian (Persero) Kanwil V Manado. Sampling technique that used inthis study is non probability sampling with purposive sampling method and datacollection was carried out using a questionnaire. The amount of sample in thisstudy are 57 sample. The analysis technique is multiple linear regression. Theresults of this study indicate that accountability accounting and competencehave a positive and significant effect on the managerial performance of PT.Pegadaian (Persero) Kanwil V Manado.